Floating buoy-based triboelectric nanogenerator for an effective vibrational energy harvesting from irregular and random water waves in wild sea. (March 2018) - Kim, Dong Yeong; Kim, Hyun Soo; Kong, Dae Sol; Choi, Moonkang; Kim, Hak Bum; Lee, Jae-Hyoung; Murillo, Gonzalo; Lee, Minbaek; Kim, Sang Sub; Jung, Jong Hoon
Abstract: Water waves in wild sea have unique characteristics of being huge, random, irregular, and of low frequency. To effectively harvest such vibrational energy, any devices should be light enough to float, sensitive even to small amplitudes, durable against harsh environmental conditions, easily replaceable after long-term use, and easily linked to form a network. Here, a floating buoy-based triboelectric nanogenerator (FB-TENG) is demonstrated to effectively harvest the vibrational energy with full satisfaction of these requirements. The FB-TENG consisted simply of a power generation unit, which was packed in an acrylic case, and a height-adjustable support, which was attached to a floating buoy. Even for the small amplitude of water waves, the height-adjustable support provides vigorous vibration at the power generation unit; which was sufficient to power 30 light-emitting diodes (LEDs), and operate a digital thermo-hygrometer and an anenometer. Under saltwater (salinity of 40%), thermal shocks (temperature range of 4–60 °C), and strong ultraviolet irradiation (power of 10 W), the FB-TENG generates stable electric power by virtue of the acrylic packing of the power generation units. The FB-TENG also generates electric power from the various and mixed amplitudes and frequencies of water waves coming from all directions. Furthermore, the FB-TENG can easily be integrated into a network for high-power generation. This work provides a significant step forward in the harvesting of the blue energy of water waves, and the realization of self-powered sea mark and weather monitoring systems in wild sea. Graphical abstract: fx1 Highlights: High power generation for small amplitude of water waves coming from all directions. Simple and safe Ar-plasma etching for the enhanced triboelectrification of PTFE. Strong resistance against harsh environmental conditions of wild sea. Self-powering of light emitting diodes, thermo-hygrometer, and anemometer.